Police Criminality: Nature and Extent of Crimes Committed by Female Police Officers. (December 2022) - Boateng, Francis D.; Hsieh, Ming-Li; Pryce, Daniel K.
Given the recent attention focusing on "bad apples" in police departments across the country, police behaviors have been the subject of considerable controversy and protest. Still, research indicates that rates of officially reported police crime are relatively low. In addition, crimes committed by female officers are largely understudied in this male-dominated workplace. Therefore, the current study explores the attributes associated with police crime committed by female officers using national arrest data. Results obtained from a multilevel model demonstrate the influences of individual- and agency-level variables in explaining female officers' criminality. Findings reveal that while on-duty female officers are more likely to commit economically motivated and drug-related crimes, off-duty officers are more likely to engage in violent and alcohol-related crimes. Moreover, contextual factors such as types of agency and numbers of sworn officers predicted female officers' criminality. Current findings highlight the importance of policies that would directly address female criminality in law enforcement.